Guidelines for Purchasing and Using Commercial Natural Enemies and Biopesticides in Florida and Other States - Norman C. Leppla; Kenneth L. Johnson (EDIS)
IPM-146, an 18-page illustrated fact sheet by Norman C. Leppla and Kenneth L. Johnson II, serves as a guide to select, purchase, and use commercially available natural enemies and biopesticides to manage accurately diagnosed pest problems. It contains a list of sources and multiple tables with information about pest problems, available natural enemies and biopesticides, and commercial suppliers. Published by the UF Department of Entomology and Nematology, May 2010.